Prevalence and determinants of early menopause before age 45 among Egyptian women based on a nationally representative survey - Saeed Soliman; Nadia M. Tawfik (Discover Public Health, 2025)
Abstract Background Premature and early menopause, defined as the cessation of menstruation before the age of 45, is associated with several long-term health risks, including cardiovascular disease, osteoporosis, and reduced life expectancy. Aim This study aimed to assess the prevalence and determinants of menopause before age 45 among Egyptian women using data from the 2014 Egyptian Demographic and Health Survey (EDHS). Methods A cross-sectional analysis was conducted on 11,016 women aged 30–45. Results The overall prevalence of early menopause was 1.9%. Significant associations were observed with socio-demographic and reproductive factors, including older age, rural residence, lower education levels, an earlier age for first sexual activity, and lack of contraception use. Multivariate analysis revealed that the likelihood of early menopause increased with age. Women in rural areas and those with no formal education had a higher prevalence of early menopause. Conclusion These findings underscore the need for early identification of women at risk of premature menopause, particularly in rural and underserved populations, to ensure timely intervention. Public health initiatives should focus on awareness campaigns and improving access to reproductive health services to mitigate the adverse health outcomes associated with early menopause.